2016
DOI: 10.21037/tau.2016.07.06
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of acquired premature ejaculation

Abstract: The second Ad Hoc International Society for Sexual Medicine (ISSM) Committee for the Definition of Premature Ejaculation defined acquired premature ejaculation (PE) as a male sexual dysfunction characterized by a the development of a clinically significant and bothersome reduction in ejaculation latency time in men with previous normal ejaculatory experiences, often to about 3 minutes or less, the inability to delay ejaculation on all or nearly all vaginal penetrations, and the presence of negative personal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 134 publications
(182 reference statements)
0
70
1
3
Order By: Relevance
“…In addition, 42% of patients that had ED that were managed by PDE5‐Is before enrollment to the study. These facts showed that patients who seek treatment for PE are varied and do not necessarily have life‐long PE, and frequently have PE combined with ED . At the present point in Japan, PE is not been well recognized as a medical condition that is treatable.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, 42% of patients that had ED that were managed by PDE5‐Is before enrollment to the study. These facts showed that patients who seek treatment for PE are varied and do not necessarily have life‐long PE, and frequently have PE combined with ED . At the present point in Japan, PE is not been well recognized as a medical condition that is treatable.…”
Section: Discussionmentioning
confidence: 99%
“…At the present point in Japan, PE is not been well recognized as a medical condition that is treatable. Subsequently, only limited patients were able to be enrolled in the present study, although the latent population who suffer from PE seems to be significant . It is necessary to increase the knowledge of PE as a common sexual condition as well as ED.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations